2011
DOI: 10.1089/lap.2010.0417
|View full text |Cite
|
Sign up to set email alerts
|

An Unusual Case of Acute Pancreatitis and Gastric Outlet Obstruction Associated with Wandering Spleen Treated by Laparoscopic Splenopexy

Abstract: Wandering spleen (WS) is an uncommon condition, usually asymptomatic, often recognized as an incidental finding. When symptoms occur, they can vary, although acute abdominal pain is the most common presentation in the pediatric population. In some cases, WS can become a dangerous condition because of the risk of splenic ischemia from persistent pedicle torsion. We describe a case of WS in a 3-year-old boy presenting with vomiting, abdominal swelling, and acute pancreatitis; the diagnosis was obtained by ultras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…The postoperative complications of splenic fixation mainly include splenic ischemia, infarction and recurrent torsion. Magno et al [ 33 ] retrospectively analyzed 125 cases of patients who underwent splenectomy and splenic fixation, and found that the incidence of postoperative complications was about 5%, including splenic infarction, recurrent volvulus, splenic ischemia, pneumothorax[ 33 ]. Fiquet-Francois et al [ 34 ] retrospectively analyzed 14 cases of patients who underwent splenic vagrant surgery in multicenter.…”
Section: Discussionmentioning
confidence: 99%
“…The postoperative complications of splenic fixation mainly include splenic ischemia, infarction and recurrent torsion. Magno et al [ 33 ] retrospectively analyzed 125 cases of patients who underwent splenectomy and splenic fixation, and found that the incidence of postoperative complications was about 5%, including splenic infarction, recurrent volvulus, splenic ischemia, pneumothorax[ 33 ]. Fiquet-Francois et al [ 34 ] retrospectively analyzed 14 cases of patients who underwent splenic vagrant surgery in multicenter.…”
Section: Discussionmentioning
confidence: 99%
“…[9] Not all patients with gastric outlet obstruction required gastropexies. A study by Magno et al [10] described the symptomatology subsided after nasogastric tube placement and no gastropexy was performed.…”
Section: Discussionmentioning
confidence: 99%
“…After derotation and splenopexy, there is no reported evidence of pancreatic injury or complication. [1011]…”
Section: Discussionmentioning
confidence: 99%
“…Bowel obstruction may occur because of the compression of abdominal organs 19 ; enuresis and hydronephrosis may be other consequences, 20 as well as gastric fundal varices, 21 mesenteric varices, 22 and acute pancreatitis. 23 The torsion of the vascular pedicle may result in splenomegaly. The progressive splenic enlargement can lead to rare splenic ruptures and to possible spontaneous massive hemoperitoneum.…”
Section: Introductionmentioning
confidence: 99%